Collaborative Strategic Mentoring Model to Improve Digital Learning Literacy Competencies (Google Meet And Canva) among School Principals - Mulyati, Puji; Apriyani, Dewi; Suriswo, Suriswo (Universitas Pahlawan Tuanku Tambusai, 2025)
Digital literacy in the era of technology-based educational transformation has become an essential competency. As educational leaders, school principals play a strategic role in ensuring the integration of digital technology in managing and developing learning at schools. However, previous research highlights a gap between the need for digital literacy in the field and the ability of school principals to utilize it effectively. Studies indicate that despite the availability of technology, digital learning has not been optimally implemented. This is attributed to the low competence of school principals in effectively using digital platforms. This research aims to develop and test the effectiveness of a strategic collaborative mentoring model as an approach to enhancing the digital literacy learning competence of school principals, particularly in using platforms like Google Meet and Canva. The study employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) design and development method, involving 40 school principals in Bojong District, Tegal Regency. The participants were divided into two groups: 20 principals in the control group and 20 principals in the experimental group. The learning tools trial was conducted using a t-test, while the effectiveness of the model was measured using the n-Gain Score test. The results indicate that the strategic collaborative mentoring model significantly improved the digital literacy learning competence of school principals. The average n-Gain Score shows a high category of improvement in the experimental group compared to the control group. The strategic collaborative mentoring model is effective in enhancing the digital literacy learning competence of school principals in supporting learning activities. This research contributes both theoretically and practically to the development of more strategic and collaborative mentoring-based training for school principals.